Black founder : the hidden power of being an outsider - Spikes, Stacy (Tantor Media, Inc., 2023)
From the award-winning entrepreneur USA Today named one of the twenty-one most influential Blacks in technology comes an empowering, bracingly honest, entertaining blueprint for success in life and work-including the true story of what really happened to MoviePass-straight from the cofounder and former CEO himself. Stacy Spikes knows what's it like to be an outsider. Finding his footing in the tech world was an education in the complexities of being an outsider-but as Stacy came to see, rather than a hindrance, it afforded him a unique position of power. Beginning as a film studio gopher, Spikes quickly rose through the industry ranks, being named one of the Hollywood Reporter's 30 Under 30. Still, he was an outsider looking in. Defying expectations, Spikes effectively disrupted the status quo and reinvented himself from junior executive to CEO Tech Founder. What ensued was an escalating adventure with bigger stages, bigger risks, and a roller-coaster ride of exhilarating ascent-unpredictable collapse-and a story book return. Taking listeners inside the battles of the boardroom and beyond, Black Founder is a business memoir that will inspire every outsider who has a dream.